Development in Southern Mexico: Empirical Verification of the "Seven Erroneous Theses about Latin America". (March 2018) - Jiménez-Bandala, Carlos Alberto
An analysis of underdevelopment and poverty in the Papaloapan Basin of southern Mexico shows that, despite the use of different development models in the neoliberal pattern of accumulation, structural conditions still promote a form of internal colonialism that enables the growth of one region at the expense of another. Recent public policies meant to support development in the region seem to be based on the dominant twentieth-century perspectives that Stavenhagen called "erroneous theses about Latin America." Un análisis del subdesarrollo y la pobreza en la cuenca del Papaloapan, en el sur de México, muestra que, a pesar del uso de distintos modelos de desarrollo dentro del patrón de acumulación neoliberal, las condiciones estructurales todavía promueven una forma de colonialismo interno que permite el crecimiento de una región a expensas de otra. Las políticas públicas receintes para apoyar el desarrollo en la región parecen estar basadas en esas perspectivas dominantes del siglo XX que Stavenhagen describió como "tesis equivocadas sobre América Latina."